Separating the Wheat from the Chaff: Icelandic and Irish Policy Responses to the Banking Crisis. (8th October 2013) - Howden, David
Abstract When the stories of the Icelandic and Irish crises are told, they are framed as if one country did everything right to exit recession and the other country everything wrong. This article assesses their recovery policies and finds that the truth lies somewhere in between. By allowing its banking system to suffer substantial losses, Iceland shielded its citizens from the costly debt overhang apparent in Ireland. Ireland's commitment to open capital markets and price deflation has allowed trade flows to remain robust, and relative prices to realign to signal sustainable production plans to entrepreneurs. These responses provide a roadmap for other small open economies with large financial sectors entering similar crises in the future.